Sertifikasi, Kompetensi, dan Inovasi Pembelajaran Dosen Perguruan Tinggi Agama Islam di Kabupaten Banyuwangi: Certification, Competence, and Learning Innovation of Lecturers at Islamic Higher Education Institutions in Banyuwangi Regency - Mundir Mundir (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2012)
This research aimed to discover whether there is a difference between lecturers who have and have not passed the certification program at Islamic Religious Colleges in Banyuwangi Regency. The population consisted of 129 lecturers (42 lecturers from STAI Ibrahimy and 87 lecturers from STAIDA Blokagung), with a sample of 65 lecturers (41 certified and 24 non-certified). Primary data were collected through questionnaires and analyzed using t-tests. The results were as follows: (1) there are significant differences in pedagogic competence; (2) there are significant differences in professional competence; (3) there were no significant differences in social competence; (4) there are significant differences in personality competence; (5) there are significant differences in innovation in learning planning; and (6) there are significant differences in innovation in the implementation of learning between certified and non-certified lecturers at Islamic Religious Colleges in Banyuwangi Regency. Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan antara dosen yang telah dan belum lulus program sertifikasi dosen di Perguruan Tinggi Agama Islam (PTAI) Kabupaten Banyuwangi. Populasi penelitian terdiri dari 129 dosen (42 dosen STAI Ibrahimy dan 87 dosen STAIDA Blokagung), dengan sampel sebanyak 65 dosen (41 dosen yang telah lulus dan 24 dosen yang belum lulus program sertifikasi). Data primer dikumpulkan melalui kuesioner dan dianalisis menggunakan uji-t. Hasil penelitian menunjukkan: (1) terdapat perbedaan signifikan dalam kompetensi pedagogik; (2) terdapat perbedaan signifikan dalam kompetensi profesional; (3) tidak terdapat perbedaan signifikan dalam kompetensi sosial; (4) terdapat perbedaan signifikan dalam kompetensi kepribadian; (5) terdapat perbedaan signifikan dalam inovasi perencanaan pembelajaran; dan (6) terdapat perbedaan signifikan dalam inovasi pelaksanaan pembelajaran antara dosen yang telah dan belum lulus program sertifikasi di PTAI Kabupaten Banyuwangi.